A process for assessing the reliability and validity of questions for use in online surveys: Exploring how communication technology is used between Lead Maternity Carer midwives and pregnant people in Aotearoa New Zealand. Issue 1 (March 2023) - Wakelin, Karen J; McAra-Couper, Judith; Fleming, Tania; Erlam, Gwen D
There is growing use of communication technology in Aotearoa New Zealand. How it is used between midwives and pregnant people is unknown. Surveys are ideal for gathering information when there is little known of a phenomenon. Aligning questions to a midwifery informed framework provides an innovate approach to explore this issue. To assess reliability and validity of questions for two online surveys using a tool created for an expert advisory group of midwives with experience in survey design and midwifery practice. An innovative approach is taken to validate questions for two online surveys using an expert advisory group of seven midwifery academic researchers with experience in both quantitative and qualitative research designs, and midwifery practice. The group were asked to rate items using a 4-point rating scale ranging from strongly agree to strongly disagree. Analysis of the scoring was undertaken using Content Validity Index, Cronbach's alpha coefficient and review of comments by the group. Quantitative scoring of both survey instruments were valid and reliable. The overall Content Validity Index score was 0.92 (midwives) and 0.93 (pregnant people). The overall Cronbach's alpha coefficient score was .78 (midwives) and .83 (pregnant people). Qualitative comments reinforced the validity and reliability of survey questions. An innovative approach was taken in assessing the reliability and validity of two online surveys using a midwifery expert advisory group and a midwifery framework to situate the surveys within a midwifery body of expertise and knowledge. The comments made by midwifery experts provided an extra layer in the validation of survey instruments using Content Validity Index and Cronbach's alpha coefficient scoring. Creating a tool for validating questions developed by midwives for an expert group of midwives recognises the potential patriarchal roots of knowledge production and dissemination and enables marginalised voices to be heard.